Fibromatosis-like spindle-cell metaplastic carcinoma of the breast – a case report - Osuchowski, Michał; Bartusik-Aebisher, Dorota; Kaznowska, Ewa; Aebisher, David (Wydawnictwo Uniwersytetu Rzeszowskiego, 2021)
Introduction. Metaplastic breast carcinoma is expressing epithelial and/or mesenchymal tissue within the same tumor. Aim. The aim of this study is to evaluate metaplastic breast carcinoma in a case report and literature review. Description of the case. The presented case desribes metaplastic carcinoma of the breast in 65 years old female patient. Conclusion. Fibromatosis-cell metaplastic carcinoma of the breast presents a particularly large diagnostic challenge. Malignant variants of this disease have been described in the literature.
Keywords: breast cancer; fibromatosis; metaplastic breast carcinoma